2022
DOI: 10.3390/ijms23116222
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mediated Response to Cancer Therapy: Modulation of Epigenetic Machinery

Abstract: Exosomes, the extracellular vesicles produced in the endosomal compartments, facilitate the transportation of proteins as well as nucleic acids. Epigenetic modifications are now considered important for fine-tuning the response of cancer cells to various therapies, and the acquired resistance against targeted therapies often involves dysregulated epigenetic modifications. Depending on the constitution of their cargo, exosomes can affect several epigenetic events, thus impacting post-transcriptional regulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Various non-coding RNAs, ranging from microRNAs (miRNAs) to long non-coding RNAs (lncRNAs) have been reported to mechanistically and functionally affect the tamoxifen resistance. Our own earlier work demonstrated a role of miR-10b in the tamoxifen resistance of ER-positive breast cancers (8) and such role of miRNAs in tamoxifen resistance has been investigated by several other researchers as well (6,7,9). Further, lncRNAs are novel molecules of interest in terms of their possible role in the modulation of response to tamoxifen in ER-positive breast cancers (10).…”
Section: Introductionmentioning
confidence: 90%
“…Various non-coding RNAs, ranging from microRNAs (miRNAs) to long non-coding RNAs (lncRNAs) have been reported to mechanistically and functionally affect the tamoxifen resistance. Our own earlier work demonstrated a role of miR-10b in the tamoxifen resistance of ER-positive breast cancers (8) and such role of miRNAs in tamoxifen resistance has been investigated by several other researchers as well (6,7,9). Further, lncRNAs are novel molecules of interest in terms of their possible role in the modulation of response to tamoxifen in ER-positive breast cancers (10).…”
Section: Introductionmentioning
confidence: 90%
“…This can lead to the activation of signaling pathways such as the mitogen activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) and PI3K/Protein kinase B (Akt) pathways, which play crucial roles in cell survival, proliferation, and differentiation [ 72 , 73 ]. Furthermore, the delivery of miRNAs by exosomes can modulate gene expression in recipient cells by affecting mRNA stability and translation, an example being the regulation of PTEN expression by exosomal miR-21, which activates the PI3K/Akt pathway [ 74 ]. The bioactive molecules present in exosomes thus impact target cells through various means, including the transfer of activated receptors and the induction of epigenetic changes, underlining the complexity and specificity of exosome-mediated communication [ 75 ].…”
Section: Biogenesis Composition and Signaling Mechanisms Of Exosomesmentioning
confidence: 99%
“…Exosomes were once thought to be the only way for cells to excrete waste products, but subsequent researches have demonstrated that exosomes function as transporters of substances, transmitters of information and biomarkers in the physiological and pathological processes of the organism ( 86 – 88 ). Exosomes are extremely significant to tumor growth, metastasis, angiogenesis and immune regulation, metabolism, and drug resistance by delivering a variety of biomolecules that mediate signal transduction ( 89 , 90 ). Exosomes, as effective biomarkers of diseases, especially cancer, have become a new research field.…”
Section: Overview Of Exosomesmentioning
confidence: 99%